Analisis Bibliografi dan Visualisasi: Strength Training on Youth Athlete - Agus, Herdiansyah; Suherman, Adang; Mubaraq, Rizqi (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2024)
Strength training has been applied with various methods for young athletes around the world, but there is little analysis that reveals research trends related to strength training in young athletes. This study bibliometrically analyzed articles from 2008 to 2023 related to the keywords strength training, resistance training, youth, and athlete. The analysis was conducted to reveal patterns of research development, articles and leading authors, journals, institutions and countries. Visualization was done using VOS viewer. The findings provide insights for the scientific field of coaching and sports talent development, especially researchers and readers to identify the development of research on strength training in young athletes as well as identify potential areas of current research. The United Kingdom was the most productive country with 49 publications and 735 citations related to strength training in youth athletes.